2017
DOI: 10.1080/22201181.2017.1317422
|View full text |Cite
|
Sign up to set email alerts
|

A pilot of the use of Short Message Service (SMS) as a training tool for anaesthesia nurses

Abstract: Background: Anaesthesia nurses form a critical part of the team providing perioperative care to patients, but no accredited training exists for them in South Africa. In this setting, short in-service training interventions are a pragmatic attempt at improving nurse performance and patient outcomes. Traditional didactic teaching formats have limitations, and mLearning (the use of mobile telephones to facilitate education) has proved equivalent or superior to traditional teaching methods in several settings. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…[4][5][6][7] In South Africa, enrolled nurses and nursing assistants with limited anaesthetic experience and training are often arbitrarily allocated to the task of anaesthetic nurse and expected to learn while performing the service. 8 The South African Society of Anaesthesiologists (SASA) acknowledges that no formal accredited training for anaesthetic nurses exists in South Africa and that the existing in-hospital programmes differ widely in their training. 9 They define a list of recommended core responsibilities of the anaesthetic nurse, but state that the responsibility of training should lie with the respective hospital, nursing and theatre managers and where applicable, the relevant department of anaesthesia.…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7] In South Africa, enrolled nurses and nursing assistants with limited anaesthetic experience and training are often arbitrarily allocated to the task of anaesthetic nurse and expected to learn while performing the service. 8 The South African Society of Anaesthesiologists (SASA) acknowledges that no formal accredited training for anaesthetic nurses exists in South Africa and that the existing in-hospital programmes differ widely in their training. 9 They define a list of recommended core responsibilities of the anaesthetic nurse, but state that the responsibility of training should lie with the respective hospital, nursing and theatre managers and where applicable, the relevant department of anaesthesia.…”
Section: Editorialmentioning
confidence: 99%
“…In this issue of SAJAA, Maharaj et al explore the work-based learning experiences of anaesthetic nurses working in five urban (regional, tertiary and central level) hospitals in eThekwini, KwaZulu-Natal. 10 Echoing the literature, 8 most anaesthetic nurses in the study received little undergraduate anaesthesia training and were anaesthetic nurses through arbitrary allocation rather than personal choice. Workplace-based training varied from one week to six months, often with limited teaching by anaesthetic doctors in the theatres.…”
Section: Editorialmentioning
confidence: 99%
“…In South Africa, the importance of the role of the anaesthetic nurse has been recognised by the South African Society of Anaesthesiologists (SASA) 1 but no formal or accredited anaesthetic nurse training programme currently exists, 2 and a lack of suitably trained anaesthetic nurses has been identified. 3 As a key assistant to the anaesthetist, an anaesthetic nurse is integral to the performance of a complex set of skills and if appropriately trained, may reduce the occurrence of anaesthesiarelated adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…The position of 'anaesthetic nurse' is most often filled by ad hoc allocation of enrolled nursing assistants (ENA) or enrolled nurses (EN) who receive no formal anaesthetic training and are expected to acquire the requisite skills 'on the job' . 2 Anecdotal information from anaesthetic nurses in our unit suggested that their limited undergraduate training often results in a significant shortfall between the knowledge and skill expected of them and the training and preparation they were exposed to. Three broad areas of importance in the training and performance of the duties of an anaesthetic nurse have been identified: the acquisition of technical skills, competency in non-technical skills and interpersonal relationships between anaesthetists and anaesthetic nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Dalam keadaan seperti ini SMS dapat diandalkan oleh Konselor Sekolah untuk menyelenggarakan assessment tanpa perlu mengkhawatirkan kecanggihan ponsel yang dimiliki siswa. SMS merupakan salah satu intervensi pendidikan yang murah, mudah diakses dan mudah dilaksanakan (Duys, Duma, & Dyer, 2017). Tidak seperti aplikasi Whatsapp; Blackberry Messenger; Messenger; Line dll, yang mengharuskan penggunaan ponsel pintar, SMS dapat digunakan pada semua ponsel dengan berbagai sistem operasi karena pemanfaatan SMS tidak terkendala oleh batasan kecanggihan HP yang dimiliki (Kert, 2011).…”
unclassified